The home: its development and care - Crawford, Lotta I. (My University, 1902)
Introduction: In this age of advancement it seems hardly necessary to impress upon the people the importance and influence of the home and yet there are many that seemingly do not know, or at least conduct their homes a manner as to lead one to think they do not know of its importance. The influence of the home upon the family and especially upon the younger members is beyond realization. “The way the twig is bent so grows the tree”—the way the child is trained in youth so he is when he becomes a man. The early training and influence of the child I what forms the foundation of his hereafter because at this time he forms his habits both good and bad. Therefore this stage of his life is the most important and his surroundings and influence should be the best at this time. That children reflect with painful truth the standards moral and social of the people about them is shown every day. “The stream can be no purer than its source.” The child reared in al all cared for home where neglect and bad influences are found, carries the mark always. When the woman takes it upon herself to be a home maker she should study the science of home making and the braches concerned in the art. Then the woman can keep her home in a sanitary and hygienic manner much better than could have been done without this knowledge and with an expenditure of less money and less time. The life of the family with all that it means to the race is absolutely dependent upon the home life. Whether we live or die and how we live or die is largely determined by the household conditions. The home in its healthy action is to the family what the body and its healthy action is to the soul.
Citation: Crawford, Lotta I. The home: its development and care. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Home Economics; Homes; Cleanliness; Appearance; Theses